Is it time to reconsider the regulatory framework for communications? OECD recommendations for the public broadcasting system in Brazil - Pieranti, Octavio Penna (2021)
In October 2020, the Organization for Economic Cooperation and Development (OECD) published two reports evaluating public policies and regulation of the communications sector in Brazil. As the country has empha- sized its interest in joining the OECD and has been adapting its procedures to the organization’s manifestations, the reports’ considerations are more rele- vant. The purpose of this paper is to analyze the OECD’s recommendations for Brazilian communication’s regulatory model, centered on the establishment of a single and convergent regulatory agency, and for public broadcasting, including the review of recent changes in EBC’s governance. Because they have been recommended by the OECD, the change in the regulatory model and advances in the sector can progress, but their effective implementation will depend on overcoming various barriers.